Raveneliapiepenbringiae and Raveneliahernandezii, two new rust species on Senegalia (Fabaceae, Mimosoideae) from Panama and Costa Rica - Ebinghaus, M. (MycoKeys, 2018)
Abstract. Two new rust species, Raveneliapiepenbringiae and R.hernandezii (Pucciniales) on Senegalia spp. (Fabaceae) are described from the Neotropics (Panama, Costa Rica). A key to the species on neotropical Senegalia spp. is provided. Molecular phylogenetic analyses based on 28S rDNA sequence data suggest that the representatives of Senegalia rusts distributed in the neotropics evolved independently from species known from South Africa. This is further supported by the teliospore morphology, which is characterised by uniseriate cysts in the neotropical Senegalia rusts and contrasting multiseriate cysts in the paleotropic Ravenelia species that infect this host genus.